Introducing the Unique Cultures from Gubugklakah and Tengger to International Citizens - Hidayat, Nurul; Wahyu Wijaya, Husni; Novianti, Vivi; Rahmadani, Desi; Yulianti, Erni (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Although thousands of tribes, with their unique characters, are scattered throughout the earth of Indonesia, the country remains intact into a single unitary state. This country's wealth is important to be introduced not only to Indonesian people, but also to international citizens. In this community service, we had the opportunity to bring University of Malaya international students to learn about one of the cultures and lives of the people of Gubugklakah and Tengger villages. This activity was done for two days and before the Covid-19 pandemic. They were even invited to live with residents to truly feel how to live in a traditional environment. The international students learned about language, ethnic, religion, way of life and the natural conservation in Indonesia. This is an important and unforgettable experience for anyone who has never touched the beauty of life in a village where the houses are not restricted by locked fences.